Can Developed Countries Make History of Poverty? - khormi, sameer (Archives of Business Research, 2020)
Since poverty is a serious issue that has had its impacts on human internationally, this paper aims to discuss poverty from different aspects and the reasons for making a history of poverty, as well as if the developed countries caused in making history of poverty. Furthermore, this paper discussed the history of poverty in the past 50 years and some initiatives have undertaken by UN and international bank to overcome the impacts of poverty in developing countries, particularly on education and healthcare. Then, a comparison was made between some developing countries how they benefited from these initiatives, while others remained poor.